MicroRNAs in colorectal cancer: translation of molecular biology into clinical application - Slaby, Ondrej; Svoboda, Marek; Michalek, Jaroslav; Vyzula, Rostislav (Molecular cancer, 2009)
MicroRNAs (miRNAs) are small non-coding RNAs 18-25 nucleotides in length that downregulate gene expression during various crucial cell processes such as apoptosis, differentiation and development. Changes in the expression profiles of miRNAs have been observed in a variety of human tumors, including colorectal cancer (CRC). Functional studies indicate that miRNAs act as tumor suppressors and oncogenes. These findings significantly extend Vogelstein's model of CRC pathogenesis and have shown great potential for miRNAs as a novel class of therapeutic targets. Several investigations have also described the ability of miRNA expression profiles to predict prognosis and response to selected treatments in CRC patients, and support diagnosis of CRC among cancer of unknown primary site. miRNAs' occurrence has been repeatedly observed also in serum and plasma, and miRNAs as novel minimally invasive biomarkers have indicated reasonable sensitivity for CRC detection and compare favorably with the fecal occult blood test. In this review, we summarize the knowledge regarding miRNAs' functioning in CRC while emphasizing their significance in pathogenetic signaling pathways and their potential to serve as disease biomarkers and novel therapeutic targets.
Keywords: mikro RNA; Gene Expression Profiling; Colorectal Neoplasms; Translational Research, Biomedical; translační biomedicínský výzkum; MicroRNAs; kolorektální nádory; Animals; lidé; polymorfismus genetický; stanovení celkové genové exprese; Molecular Biology; zvířata; Humans; molekulární biologie; Polymorphism, Genetic